Comparison of phase disposition, phase opposition, and phase disposition with variable frequency PWM techniques for harmonic reduction in cascaded multilevel inverters - G. Nayana; Savita D. Torvi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
Renewable energy penetration in distributed generation systems significantly impacts the power quality of the output. The stochastic nature of the inverters provides variable voltage and variable frequency outputs, which is an advantage when used with photovoltaic (PV) and grid integration to the distribution grid, and also in induction motor drives. A primary source of power quality issues is the harmonics generated by the inverters. Multilevel inverters are commonly employed to mitigate these harmonics and improve power quality. Among the various multilevel inverter topologies, the cascaded multilevel inverter (CMLI) has gained prominence due to its simple structure, ease of control, and reduced component requirements. This paper presents a comprehensive review of multilevel inverter topologies that have influenced the evolution of the CMLI structure, along with an investigation into the application of advanced pulse width modulation (PWM) strategies for performance enhancement. In particular, phase disposition (PD), phase opposition disposition (POD), and phase disposition with variable frequency (PD-VF) PWM techniques are implemented on cascaded h-bridge (CHB) multilevel inverters configured for five-level, seven-level, and nine-level operations. A comparative evaluation of total harmonic distortion (THD) is conducted for each inverter configuration, both with and without the inclusion of an LC output filter, to assess waveform quality and harmonic mitigation capability. Furthermore, the harmonic suppression effectiveness of PD, POD, and PD-VF modulation methods is systematically analyzed across different voltage levels. The study also demonstrates that varying the carrier frequency in PD-VF modulation significantly influences THD performance, offering enhanced flexibility and expanded control possibilities in multilevel inverter applications.